Constitutional Regulation and Protection of Personal Rights and Freedom in Uzbekistan - MELIEVICH, MUKHAMMEDOV HAYDARALI (The journal of contemporary issues in business and government, 2021)
The abstract in the article examines human dignity as the initial principle of the general legal principle of humanism. The author pays attention to human dignity - the basis of the rights and freedoms of the individual, the right to the dignity of the individual as a subjective right of a citizen, the forms and mechanisms of protecting the dignity of the individual in the branches of law, compensation for moral harm in protecting the dignity of the individual: moral and legal problems. Studied the dignity of the person in the conditions of the formation of civil society in Uzbekistan during the pandemic: legal aspects.